TEACHING ENGLISH VOCABULARY USING SPELLING GAMES FOR INDONESIAN KINDERGARTEN STUDENTS: A CASE STUDY - Sugeng Susilo Adi; Ricky Chandra Wijaya (Erudio Journal of Educational Innovation, 2018)
Indonesian students started learning English from kindergarten with the purpose of intruducing basic English vocabulary as a component from language material in learning English. Teaching English vocabulary is one of the important language skills. This research tries to describe the use of spelling game in teaching vocabulary to kindergarten students. The data were analyzed using qualitative descriptive analysis. The subjects were students of Children Center Brawijaya Smart School A & B. That class consists of fifty students divided into four small classes. For completing the data, the researcher used questionnaire, interview, observation checklist and video recording to record the teaching and learning process. The result exposes that the teaching strategies mostly used were listen and repeat, listen and do, draw and color, and the spelling strategies mostly used was phonetic spelling strategies. For the Language games mostly used was movement game, card game, drawing game and word game. From analysis it was implied that the effectiveness of spelling games at Children Center Brawijaya Smart School in teaching English vocabulary can be classified to the category “very good”. It is suggested to the teacher try to be using various media in order to support the learning process in the class, to be able to make the individual approaches well. Finally, it is recommended to the further researcher to maximize the result and improve the weakness of this research for make a better research analysis.